2018
DOI: 10.1074/jbc.ra118.004092
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae Hrq1 and Pif1 DNA helicases synergistically modulate telomerase activity in vitro

Abstract: Telomere length homeostasis is vital for maintaining genomic stability and is regulated by multiple factors, including telomerase activity and DNA helicases. The Pif1 helicase was the first discovered catalytic inhibitor of telomerase, but recent experimental evidence suggests that Hrq1, the yeast homolog of the disease-linked human RecQ-like helicase 4 (RECQL4), plays a similar role via an undefined mechanism. Using yeast extracts enriched for telomerase activity and an primer extension assay, here we determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 61 publications
5
45
0
Order By: Relevance
“…We recently found that Pif1 impacts in vitro telomerase activity in a biphasic manner: low concentrations of Pif1 increase telomerase activity, but high Pif1 concentrations decrease telomerase activity [14]. Using a 15-nt telomerase repeat sequence (TG 1-3 ) oligonucleotide substrate (Tel15), an S. cerevisiae extract enriched for telomerase activity, and recombinant Pif1, we demonstrated a similar phenomenon here in Figure 2A,B.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…We recently found that Pif1 impacts in vitro telomerase activity in a biphasic manner: low concentrations of Pif1 increase telomerase activity, but high Pif1 concentrations decrease telomerase activity [14]. Using a 15-nt telomerase repeat sequence (TG 1-3 ) oligonucleotide substrate (Tel15), an S. cerevisiae extract enriched for telomerase activity, and recombinant Pif1, we demonstrated a similar phenomenon here in Figure 2A,B.…”
Section: Resultssupporting
confidence: 67%
“…Chemical reagents were purchased from Sigma or DOT Scientific (Burton, MI, USA). All recombinant proteins were purified as described in [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Just recently, Hrq1, a DNA helicase that has similarity to the human RecQ helicase RecQL4 [142], was shown to functionally interact with ScPif1 to synergistically modulate telomere length homeostasis by regulating telomerase activity [143]. Depending on whether the ScPif1 helicase or the Hrq1 helicase was active, telomerase was either inhibited or stimulated, and the authors propose that post-translational modifications that modulate the helicase activity of either one, such as already shown for ScPif1 [144,145], could thus regulate telomerase activity [143].…”
Section: Telomere Length Maintenancementioning
confidence: 99%